2014
DOI: 10.1037/a0036742
|View full text |Cite
|
Sign up to set email alerts
|

Intake-dependent effects of cocaine self-administration on impulsive choice in a delay discounting task.

Abstract: Cocaine use is associated with high levels of impulsive choice (greater discounting of delayed rewards) in humans, but the cause/effect relationships between cocaine use and impulsive choice are not fully understood. In previous work, we found that both experimenter- and self-administration of fixed quantities of cocaine caused lasting increases in impulsive choice in rats. The present study extended these findings by taking into account baseline impulsive choice prior to self-administration, and by allowing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 99 publications
(176 reference statements)
4
41
1
Order By: Relevance
“…Alterations in delay discounting are often studied after acute drug exposure; however, cocaine administration may cause long-lasting elevations in impulsive choice as measured by delay discounting [27, 147, 148], a finding consistent with the human literature mentioned above. Perhaps the most compelling evidence for long-term alterations in impulsive choice as a result of cocaine exposure is in rhesus monkeys.…”
Section: Underlying Neurocircuitry Of Impulsivitiessupporting
confidence: 62%
See 1 more Smart Citation
“…Alterations in delay discounting are often studied after acute drug exposure; however, cocaine administration may cause long-lasting elevations in impulsive choice as measured by delay discounting [27, 147, 148], a finding consistent with the human literature mentioned above. Perhaps the most compelling evidence for long-term alterations in impulsive choice as a result of cocaine exposure is in rhesus monkeys.…”
Section: Underlying Neurocircuitry Of Impulsivitiessupporting
confidence: 62%
“…Greater discounting of the large reward (e.g. steeper discounting) is indicative of a more impulsive animal [26, 27]. …”
Section: Measures Of Impulsivitymentioning
confidence: 99%
“…One issue is that treatments that reduced impulsivity led to an increased preference for the large cocaine alternative, which typically would result in increased drug intake, which was observed in males in the present study (see Figure 3). Another difficulty is that the reduction in impulsive choice observed here was due to the drug treatments interacting with the behaviorally disruptive (Smethells and Carroll 2015) or impulsivity-increasing effects of acute and chronic cocaine exposure (e.g., Broos et al 2012a; Dandy and Gatch 2009; Mitchell et al 2014; Simon et al 2007; but see Winstanley et al 2007). Regardless of these issues, the reduction in impulsive choice for cocaine provides support for employing the present treatments given the strong relationship between drug abuse and impulsive choice (see Madden and Bickel, 2010, for a review).…”
Section: Discussionmentioning
confidence: 96%
“…Anorexia nervosa is 13 times more prevalent in females than males (McCarthy et al 2012) and is associated with pathological risk aversion (Kaye et al 2013). Finally, there are considerable sex differences in SUD (Becker et al 2012; Carroll et al 2004; Lynch 2006), which has been shown in both preclinical and human studies to be associated with increased impulsive choice and risk-taking behavior (Anker et al, 2009; Bechara et al 2001; Gowin et al 2013; Mitchell et al 2014a; Mitchell et al 2014b). Thus, differences in decision-making between males and females could be linked to each sex’s predisposition to specific psychiatric conditions.…”
Section: Discussionmentioning
confidence: 99%